Non-pharmacological interventions for delirium in the pediatric population: a systematic review with narrative synthesis - Kyua Kim; Ju Hee Jeong; Eun Kyoung Choi (BMC, 2024)
Abstract Background Delirium is a serious complication experienced by hospitalized children. Therefore, preventive management strategies are recommended for these patients. However, comprehensive analyses of delirium interventions in children remain insufficient. Specifically, this systematic review aimed to summarize non-pharmacological interventions for pediatric delirium, addressing the urgent need for a comprehensive understanding of effective strategies. We also explored frequently measured outcome variables to contribute evidence for future research on delirium outcomes in children. Methods This systematic review searched articles from PubMed, Web of Science, Cumulative Index to Nursing and Allied Health Literature, and Excerpta Medica databases. The eligibility criteria were formed under the population, intervention, comparator, outcome, and study design framework. Studies were included if they involved (1) children aged under 18 years receiving hospital care, (2) non-pharmacological delirium interventions, (3) comparators involving no intervention or pharmacological delirium interventions, and (4) outcomes measuring the effectiveness of non-pharmacological delirium interventions. Only peer-reviewed articles published in English were included. Results Overall, 16 studies were analyzed; of them, 9 assessed non-pharmacological interventions for emergence delirium and 7 assessed interventions for pediatric delirium. The intervention types were grouped as follows: educational (n = 5), multicomponent (n = 6), and technology-assisted (n = 5). Along with pediatric and emergence delirium, the most frequently measured outcome variables were pain, patient anxiety, parental anxiety, pediatric intensive care unit length of stay, agitation, analgesic consumption, and postoperative maladaptive behavior. Conclusions Non-pharmacological interventions for children are effective treatments without associated complications. However, determining the most effective non-pharmacological delirium intervention for hospitalized children based on current data remains challenging.